The Phenicien Carthaginian Purple Industry and Contemporary Design: An Intersection between Cultural Heritage, Sustainability and Creativity - Kallel, Houda Kohli; Falhi, Soumaya Gharsallah (Proceedings of the 2025 International Conference on Global Cultural and Creative Industries (ICGCCI 2025), 2025)
Fashion and cultural heritage play an essential role in preserving traditional skills and indigenous knowledge. In a context of globalisation, these aspects become vectors of transcultural creativity, particularly in interdisciplinary design projects. This summary examines how industry and the purple colour of the Carthaginians influence contemporary designers in various creative fields, while exploring the impact of sustainability and art on these practices. The methodological approach of this study is based on a qualitative analysis of the creative and craft practices of the Carthaginians, in particular their purple colour industry. An exploration of historical and cultural references was used to identify elements of traditional knowhow. Next, an analysis of the work of designers in the fields of fashion, graphic design and product design will be interpreted to understand how the crimson industry influences their creations. The results show that the Carthaginian purple industry, a symbol of power and prestige, is a major inspiration for contemporary designers. This rare pigment, extracted from molluscs, was once used to dye the clothes of the elite. Today, it is being reinterpreted in design projects, underlining the importance of sustainability and respect for natural resources. The designers interviewed highlighted the influence of the colour's cultural symbolism, as well as its aesthetic appeal in sectors such as fashion, interior design and graphics.This research reveals that the intersection of art, sustainability and design can act as a catalyst to revive craft traditions, while offering endless creative possibilities. Designers are drawing on Carthaginian heritage to develop innovative creations, adoping practices that are more respectful of the environment. In this way, traditional craftsmanship becomes a source of inspiration for contemporary creation, linking past and present.
Keywords: Artisanat -- Djerba; Murex -- Djerba

في قلالة بجزيرة جربة مازالت النساء يتجملن بالحولي (Babnet, 2025)
مازالت المرأة في منطقة قلالة بجزيرة جربة تصر على ارتداء اللباس التقليدي المستوحى أساسا من الموروث الامازيغي والمعروفبالمناشف أو الحولي. هو لباس يومي
Keywords: Artisanat -- Djerba; Moeurs et coutumes -- Djerba